Teachers Digital Strategies in Teaching English Vocabulary to Kindergarten Students at RA Raudhatul Jannah - Tiara Noviarini (EXPOSE (Journal of English Education and for Specific Purpose), 2025)
Vocabulary acquisition is a fundamental component of early English language learning, particularly in kindergarten contexts where learners rely heavily on concrete and meaningful input. This study aimed to investigate the digital strategies employed by teachers in teaching English vocabulary to young learners and to explore teachers pedagogical considerations in integrating digital media into classroom instruction. The research adopted a qualitative descriptive design with a case study approach. Data were collected through non-participant classroom observations, semi-structured interviews with three kindergarten teachers and one school principal, and documentation of digital learning materials. The data were analyzed using data reduction, data display, and conclusion drawing techniques, supported by triangulation to ensure credibility. The findings revealed that teachers employed several digital strategies, including animated instructional videos, interactive digital applications, audiovisual English songs, and digital vocabulary games. These strategies were implemented in a structured, teacher-guided manner to introduce, reinforce, and assess vocabulary learning. Digital media were primarily used to provide visual and auditory support, facilitate repetition, sustain students engagement, and create a positive learning atmosphere. The study also found that teachers consciously limited screen time and combined digital activities with interactive follow-up practices to maintain active learning. These results indicate that digital media can effectively support vocabulary instruction when integrated with developmentally appropriate pedagogy. Based on the findings, this study suggests that early childhood educators should be supported in developing digital pedagogical competence through training and institutional support. Educational stakeholders are encouraged to promote the thoughtful use of digital media that aligns with young learners cognitive and emotional needs. Future educational practices should emphasize pedagogically driven technology integration rather than technology-centered instruction.